Modern recommendations on children's baseline cardiopulmonary resuscitation (BLS 2010) - R.F. Tepaev; Y.V. Zhirkova; A.S. Belousova; E.I. Ilyicheva (Union of pediatricians of Russia, 2012)
The main reason for children's and adolescents' mortality in Russia is external causes, such as injuries, poisonings, drownings and road traffic collisions. Many of the external causes may be prevented. Besides, the popularization of modern baseline cardiopulmonary resuscitation methods is one the methods of mortality reduction in children on the pre-hospital stage. The article gives children's baseline cardiopulmonary resuscitation basics recommended by the American Heart Association.Key words: cardiopulmonary resuscitation, children, adolescents.